A Decade Review of Dinoflagellate Species Composition in Lombok Waters, West Nusa Tenggara: Threat or Blessing - Mujib, Abd. Saddam; Dermawan, Awan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Armiani, S. (2021). Komposisi dan Kelimpahan Jenis Fitoplankton di Perairan Pelabuhan Carik Kecamatan Bayan Kabupaten Lombok Utara. Jurnal Ilmiah Pendidikan Sains Dan Terapan, 1(1), 75–80. Asefi, M. A., & Attaran-Fariman, G. (2022). A Review of the Biotoxin of Marine Dinoflagellates; Mechanism of Action, Methods of Analysis, and Effects of These Toxins on the Environment and Human. Journal of Marine Medicine Spring, 2022(1), 68–78. https://doi.org/10.30491/4.1.68 A Asri, Y., Cokrowati, N., Sumsanto, M., & Diniariwisan, D. (2024). Abundance Index And Community Structure Of Phytoplankton In The Integrated Marine Aquaculture Area Of Ekas Bay , West Nusa Tenggara. Jurnal Perikanan, 14(4), 2116–2125. https://doi.org/http://doi.org/10.29303/jp.v14i4.1256 Ayache, N., Bill, B. D., Brosnahan, M. L., Campbell, L., Deeds, J. R., Fiorendino, J. M., Gobler, C. J., Handy, S. M., Harrington, N., Kulis, D. M., McCarron, P., Miles, C. O., Moore, S. K., Nagai, S., Trainer, V. L., Wolny, J. L., Young, C. S., & Smith, J. L. (2023). A survey of Dinophysis spp. and their potential to cause diarrhetic shellfish poisoning in coastal waters of the United States. Journal of Phycology, 59(4), 658–680. https://doi.org/10.1111/jpy.13331 Baek, S. H., Shimode, S., Han, M. S., & Kikuchi, T. (2008). Growth of dinoflagellates, Ceratium furca and Ceratium fusus in Sagami Bay, Japan: The role of nutrients. Harmful Algae, 7(6), 729–739. https://doi.org/10.1016/j.hal.2008.02.007 Barber-Lluch, E., Nieto-Cid, M., Santos-Echeandía, J., & Sánchez-Marín, P. (2023). Effect of dissolved organic matter on copper bioavailability to a coastal dinoflagellate at environmentally relevant concentrations. Science of the Total Environment, 901(May). https://doi.org/10.1016/j.scitotenv.2023.165989 Basti, L., Uchida, H., Matsushima, R., Watanabe, R., Suzuki, T., Yamatogi, T., & Nagai, S. (2015). Influence of temperature on growth and production of pectenotoxin-2 by a monoclonal culture of Dinophysis caudata. Marine Drugs, 13(12), 7124–7137. https://doi.org/10.3390/md13127061 Bui, Q. T. N., Kim, H., Park, H., & Ki, J. S. (2021). Salinity affects saxitoxins (Stxs) toxicity in the dinoflagellate alexandrium pacificum, with low transcription of sxt-biosynthesis genes sxta4 and sxtg. Toxins, 13(10). https://doi.org/10.3390/toxins13100733 Carnicer, O., Irwin, A. J., & Finkel, Z. V. (2022). Traits influence dinoflagellate C:N:P. European Journal of Phycology, 57(2), 154–165. https://doi.org/10.1080/09670262.2021.1914860 Coyne, K. J., Salvitti, L. R., Mangum, A. M., Ozbay, G., Main, C. R., Kouhanestani, Z. M., & Warner, M. E. (2021). Interactive effects of light, CO2 and temperature on growth and resource partitioning by the mixotrophic dinoflagellate, Karlodinium veneficum. PLoS ONE, 16(10 October), 1–20. https://doi.org/10.1371/journal.pone.0259161 Dolatabadi, F., Attaran-Fariman, G., & Loghmani, M. (2021). Bloom occurrence and phylogeny of Gonyaulax polygramma (Dinophyceae) isolated from south east coast of Iran (Oman Sea). Iranian Journal of Fisheries Sciences, 20(6), 1789–1803. https://doi.org/10.22092/ijfs.2021.125501 Dong, S., Lei, Y., Bi, H., Xu, K., Li, T., & Jian, Z. (2022). Biological Response of Planktic Foraminifera to Decline in Seawater pH. Biology, 11(1), 1–12. https://doi.org/10.3390/biology11010098 Fathurrahman, & Aunurohim. (2014). Kajian Komposisi Fitoplankton dan Hubungannya dengan Lokasi Budidaya Kerang Mutiara (Pinctada Maxima) di Perairan Sekotong, Nusa Tenggara Barat. Teknik Pomits, 3(2), 93–98. Fernández, R., Mamán, L., Jaén, D., Fuentes, L. F., Ocaña, M. A., & Gordillo, M. M. (2019). Dinophysis species and diarrhetic shellfish toxins: 20 years of monitoring program in andalusia, south of spain. Toxins, 11(4). https://doi.org/10.3390/toxins11040189 Fitriyah, A., Zainuri, M., & Indriyawati, N. (2022). Perbedaan dan Hubungan Nitrat, Fosfat Dengan Kelimpahan Fitoplankton Pada Saat Air Pasang dan Surut di Muara Ujung Piring Bangkalan. Jurnal Kelautan: Indonesian Journal of Marine Science and Technology, 15(1), 60–68. https://doi.org/10.21107/jk.v15i1.13990 Funaki, C., Kuwata, K., Lum, W. M., Takahashi, K., Iwataki, M., & Takahashi, K. (2024). Effects of temperature and light intensity on growth in Prorocentrum cf . balticum ( Dinophyceae ) isolated from the Oyashio-Kuroshio Mixed Water region , North Pacific. Plankton and Benthos Research, 19(4), 191–202. https://doi.org/10.3800/pbr.19.191 Graeff, J. E., Elkins, L. C., Leblond, J. D., Graeff, J. E., Elkins, L. C., & Leblond, J. D. (2021). Plastid-associated galactolipid composition in eyespot-containing dinoflagellates: a review. Algae, 36(2), 73–90. https://doi.org/https://doi.org/10.4490/algae.2021.36.5.25 Iskandar, I., Sukoco, N. B., Kamija, K., & Pranowo, W. S. (2022). Karakteristik Termoklin dan Kecepatan Suara di Selat Lombok Berdasarkan Filtering data CTD Menggunakan Analysis Toolpak. Jurnal Chart Datum, 4(1), 43–50. https://doi.org/10.37875/chartdatum.v4i1.3 Ismunarti, D. H., & Baskoro, R. (2013). Kajian Pola Arus Di Perairan Nusa Tenggara Barat Dan Simulasinya Menggunakan Pendekatan Model Matematik. Buletin Oseanografi Marina, 2, 5–6. Kesaulya, I., Rumohoira, D. R., & Saravanakumar, A. (2022). The Abundance of Gonyaulax polygramma and Chaetoceros sp. Causing Blooming in Ambon Bay, Maluku. Ilmu Kelautan: Indonesian Journal of Marine Sciences, 27(1), 13–19. https://doi.org/10.14710/ik.ijms.27.1.13-19 Mahmudi, M., Arsad, S., Lusiana, E. D., Musa, M., Fitrianesia, F., Ramadhan, S. F., Arif, A. R., Savitri, F. R., Dewinta, A. A., & Ongkosongo, A. D. (2023). Microalgae diversity in varying habitat characteristics in Pasuruan and Sidoarjo coastal areas, East Java, Indonesia. Biodiversitas, 24(8), 4418–4426. https://doi.org/10.13057/biodiv/d240823 Matsubara, T., Nagasoe, S., Yamasaki, Y., Shikata, T., Shimasaki, Y., Oshima, Y., & Honjo, T. (2007). Effects of temperature, salinity, and irradiance on the growth of the dinoflagellate Akashiwo sanguinea. Journal of Experimental Marine Biology and Ecology, 342(2), 226–230. https://doi.org/10.1016/j.jembe.2006.09.013 Mujib, A. S., Damar, A., & Wardiatno, Y. (2015). Spatial Distribution of Planktonic Dinoflagellate in Makassar Waters, South Sulawesi. Jurnal Ilmu Dan Teknologi Kelautan Tropis, 7, 479–492. Park, S. A., Jeong, H. J., Ok, J. H., Kang, H. C., You, J. H., Eom, S. H., Du Yoo, Y., & Lee, M. J. (2024). Effect of salinity on the bioluminescence intensity of the heterotrophic dinoflagellates Noctiluca scintillans and Polykrikos kofoidii and the autotrophic dinoflagellate Alexandrium mediterraneum. Marine Biology, 171(6), 1–19. https://doi.org/10.1007/s00227-024-04440-3 Paulette, A. M. (2023). Phycotoxins Dynamic from San-Pedro Port Area and their Potentials Associated Risks. European Journal of Applied Science, 11(5), 121–131. https://doi.org/10.14738/aivp.115.15187 Perkins, J. C., Zenger, K. R., Kjeldsen, S. R., Liu, Y., & Strugnell, J. M. (2025). Assessment of dinoflagellate diversity using DNA metabarcoding reveals toxic dinoflagellate species in Australian coastal waters. Marine Pollution Bulletin, 210(November 2024), 117319. https://doi.org/10.1016/j.marpolbul.2024.117319 Purnamaningtyas, S. E. (2019). Distribusi dan Kelimpahan Fitoplankton di Teluk Gerupuk, Nusa Tenggara Barat. Akuatika Indonesia, 4(1), 24. https://doi.org/10.24198/jaki.v4i1.23431 Radiarta, I. N., Erlania, E., & Ketut Sugama, K. S. (2015). Analisis Spasial Dan Temporal Komunitas Fitoplankton Sekitar Budidaya Laut Terintegrasi Di Teluk Ekas, Nusa Tenggara Barat. Jurnal Riset Akuakultur, 10(2), 283. https://doi.org/10.15578/jra.10.2.2015.283-291 Sathishkumar, R. S., Sahu, G., Mohanty, A. K., Arunachalam, K. D., & Venkatesan, R. (2021). First report of Protoperidinium steinii (Dinophyceae) bloom from the coastal marine ecosystem – an observation from tropical Indian waters. Oceanologia, 63(3), 391–402. https://doi.org/10.1016/j.oceano.2021.04.003 Sherr, E. B., & Sherr, B. F. (2007). Heterotrophic dinoflagellates: A significant component of microzooplankton biomass and major grazers of diatoms in the sea. Marine Ecology Progress Series, 352, 187–197. https://doi.org/10.3354/meps07161 Syaufullah, M. D. (2015). Analisis Suhu Permukaan Laut Perairan Indonesia...Pemanasan Global (Syaifullah. Jurnal Segara, 11(1), 37–47. http://rda.ucar.edu/datasets/ Watras, C. J., Chisholm, S. W., & Anderson, D. M. (1982). Regulation of growth in an estuarine clone of Gonyaulax tam arensis Lebour: Salinity-dependent temperature responses. Journal of Experimental Marine Biology and Ecology, 62(1), 25–37. https://doi.org/10.1016/0022-0981(82)90214-3 Ye, M. H., Li, D. W., Cai, Q. D., Jiao, Y. H., Liu, Y., Li, H. Y., & Yang, W. D. (2022). Toxic Responses of Different Shellfish Species after Exposure to Prorocentrum lima, a DSP Toxins Producing Dinoflagellate. Toxins, 14(7). https://doi.org/10.3390/toxins14070461